A low magnetic noise level glass steel dewar liner and a preparation method thereof

CN115727256BActive Publication Date: 2026-10-09BEIJING MILESTONE SCI & TECH DEV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202111013910.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-31
Publication Date
2026-10-09
Estimated Expiration
2041-08-31

AI Technical Summary

Technical Problem

[0005]鉴于上述的分析,本发明实施例旨在提供一种低磁噪声水平玻璃钢杜瓦内胆及其制备方法,用以解决现有杜瓦材料磁噪声水平较高的问题

Benefits of technology

1、本发明通过芯轴表面预先缠绕聚四氟乙烯胶带,预浸改性树脂的玻璃纤维带在工艺张力作用下,缠绕于预热的金属芯轴上,固化成型,得到低磁噪声水平玻璃钢杜瓦内胆;本发明的低磁噪声水平玻璃钢杜瓦内胆在频繁的热循环(液氦-室温)作用下可持久稳定使用,不仅降低设备更换成本,同时降低液氦消耗成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115727256B_ABST
    Figure CN115727256B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of low magnetic noise level glass steel dewar liner and its preparation method, belong to the technical field of glass steel composite material, solve the problem that dewar material must first from material selection and manufacturing process to solve the higher magnetic noise level of itself in prior art.Dewar liner includes modified resin, glass fiber belt, its preparation method is by pre-winding polytetrafluoroethylene adhesive tape on the surface of mandrel, the glass fiber belt of pre-impregnated modified resin is wound on preheated metal mandrel under the action of process tension, and is cured to form.The low magnetic noise level glass steel dewar liner obtained by the present application has an inner diameter of 15-250mm, a wall thickness of 1-6mm, a length of 10-1100mm, and a magnetic noise level of 10 ‑14 ~10 ‑15 T, which meets the use requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of fiberglass composite materials, and more particularly to a low-magnetic-noise level fiberglass Dewar liner and its preparation method. Background Technology

[0002] A superconducting quantum interference device (SQUID) is a highly sensitive detector used to study the formation and changes of the Earth, measure the induced magnetization of the Earth, locate mineral deposits and underground resources, perform precise measurements of the geomagnetic field, paleomagnetic field measurements, detect the location of submarines on the seabed, and detect changes in biomagnetic fields. The basic requirements for the operating environment of a SQUID are a non-magnetic, vibration-free, and ultra-low temperature environment (liquid helium). A Dewar radiator is used to provide the ultra-low temperature environment for the superconducting components to operate. In principle, SQUIDs are used to detect weak magnetic signals, and the Dewar radiator material must first address its own magnetic noise level through material selection and manufacturing processes. Therefore, a low magnetic noise level is a core indicator determining its application.

[0003] Currently, relevant research has been conducted in China, mainly focusing on the study of Dewar structures.

[0004] For example, Chinese invention patent CN201410809764.5 discloses an airborne magnetic measurement device based on a low-temperature superconducting SQUID, and describes the structural composition of the device. Chinese invention patent CN202110145543.2 discloses a low-temperature system and a superconducting quantum interference system, and describes the structural composition of the system. Chinese invention patent CN201210122287.6 discloses a non-metallic, non-magnetic liquid nitrogen Dewar, and describes the structural composition of the Dewar. Therefore, achieving a low magnetic noise level in the fiberglass Dewar liner is a decisive factor in its application. Summary of the Invention

[0005] Based on the above analysis, the present invention aims to provide a low-magnetic-noise level fiberglass Dewar liner and its preparation method, in order to solve the problem of high magnetic noise level in existing Dewar materials.

[0006] On one hand, the present invention provides a low-magnetic-noise level fiberglass Dewar liner, wherein the liner comprises, by weight percentage: 50-70% fiberglass tape and 30-50% modified resin; the magnetic noise level of the fiberglass Dewar liner is 10. -14 ~10 -15 T.

[0007] Furthermore, the modified resin is a modified bisphenol F type epoxy resin, the modifier is polyurethane, and the mass ratio of bisphenol F type epoxy resin to polyurethane is 9:1.

[0008] Furthermore, the aforementioned glass fiber tape is an alkali-free aluminosilicate glass fiber tape.

[0009] Furthermore, the aforementioned inner liner is obtained by curing glass fiber tape pre-impregnated with modified resin.

[0010] Furthermore, the aforementioned inner liner is formed by curing a glass fiber tape pre-impregnated with modified resin wound around a mandrel.

[0011] Furthermore, the aforementioned mandrel is pre-wound with polytetrafluoroethylene tape.

[0012] On the other hand, the present invention provides a method for preparing a low-magnetic-noise level fiberglass Dewar liner, comprising the following steps: Step S1: Impregnate the glass fiber tape with modified resin liquid and draw a vacuum to fully impregnate the glass fiber tape with modified resin, remove gas inclusions, and obtain a pre-impregnated glass fiber tape. Step S2: The surface of the metal mandrel is pre-wrapped with polytetrafluoroethylene tape, and then the mandrel is preheated; Step S3: Wrap the pre-impregnated glass fiber tape obtained in step S1 around the outer surface of the polytetrafluoroethylene tape of the preheated metal mandrel; Step S4: Place the spiral tube obtained in step S3 into an insulation box and cure the modified resin in the insulation box; Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after cooling, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

[0013] Furthermore, in step S1 above, the glass fiber tape has a width of 20-50 mm, a thickness of 0.05-0.2 mm, a K2O+Na2O mass percentage of less than 0.3%, and an iron oxide content of less than 0.1%.

[0014] Furthermore, in step S1 above, the mass ratio of the glass fiber tape to the modified resin liquid in the pre-impregnated glass fiber tape is 5-7:3-5.

[0015] Furthermore, in step S1 above, the glass fiber tape is impregnated for 2–5 hours, and the vacuum degree is 10. -2 ~10 -3 MPa.

[0016] Furthermore, in step S2 above, the mandrel is pre-wound with polytetrafluoroethylene tape, the overlap of the spiral winding is 30~50%, and the mandrel is preheated to 80~90°C.

[0017] Furthermore, in step S3 above, the pre-impregnated glass fiber tape is wound around the outer surface of the polytetrafluoroethylene tape of the preheated metal mandrel, with a process tension of 0.5 MPa; the winding thickness of the pre-impregnated glass fiber tape is 1~6 mm.

[0018] Furthermore, in step S4 above, the curing temperature is 80–200°C and the curing time is 2–4 hours.

[0019] Furthermore, the inner liner obtained in step S5 has an inner diameter of 15–250 mm, a wall thickness of 1–6 mm, a length of 10–1100 mm, and a magnetic noise level of 10. -14 ~10 -15 T.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. This invention involves pre-winding polytetrafluoroethylene tape around the surface of a mandrel, and then winding pre-impregnated modified resin-coated glass fiber tape onto a preheated metal mandrel under process tension, followed by curing to obtain a low-magnetic-noise level fiberglass Dewar liner. The low-magnetic-noise level fiberglass Dewar liner of this invention can be used stably and for a long time under frequent thermal cycling (liquid helium-room temperature), which not only reduces equipment replacement costs but also reduces liquid helium consumption costs.

[0021] 2. The low magnetic noise level fiberglass Dewar liner of the present invention has a low magnetic noise level, an inner diameter of 15-250 mm, a wall thickness of 1-6 mm, a length of 10-1100 mm, and a density of 1.84-1.86 g / cm³. 3 Strength and elasticity tests were conducted. The warp tensile strength was 310–318 MPa, the weft tensile strength was 304–315 MPa, the compressive strength perpendicular to the layers was 466–472 MPa, the shear strength parallel to the layers was 44.5–46 MPa, the flexural strength perpendicular to the layers was 384–387 MPa, and the flexural modulus of elasticity was 2.48–2.51 GPa. The magnetic noise level was tested to be 10. -14 ~10 -15 T has excellent performance and meets the requirements for SQUID usage.

[0022] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0023] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0024] Figure 1 is a front view of the winding structure in the preparation of the fiberglass Dewar liner of the present invention; Figure 2 This is a side view of the winding structure used in the fabrication of the fiberglass Dewar liner of this invention.

[0025] Figure label: 1-Mandrel; 2-PTFE tape; 3-Pre-impregnated fiberglass tape. Detailed Implementation

[0026] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0027] On one hand, this invention discloses a low-magnetic-noise level fiberglass Dewar liner, which, by weight percentage, comprises: 50-70% fiberglass tape and 30-50% modified resin; the inner diameter of the liner is 15-250 mm, the wall thickness is 1-6 mm, the length is 10-1100 mm, and the magnetic noise level is 10. -14 ~10 -15 T.

[0028] Specifically, the glass fiber tape accounts for 50-70%, and the modified resin accounts for 30-50%; the ratio of the two is controlled by the impregnation process and can be calculated from the weight of the glass fiber before and after impregnation.

[0029] Specifically, the aforementioned glass fiber tape is an alkali-free aluminosilicate glass fiber tape with a width of 20–50 mm and a thickness of 0.05–0.2 mm; glass fiber tape of this size is easy to control for flatness during winding.

[0030] Specifically, the glass fiber tape contains less than 0.3% K2O and Na2O impurities by mass and less than 0.1% iron oxide impurities.

[0031] It should be noted that K2O and Na2O are common in glass fibers. This invention preferably uses alkali-free aluminosilicate glass fiber tape, whose K2O and Na2O content is generally no more than 0.5%. However, since the K2O and Na2O content directly affects the tensile strength of the glass fiber, and tensile strength is a crucial factor in the practical application of Dewar liners, the content of impurities K2O and Na2O in the glass fiber tape must be further controlled. The sum of their mass percentages should be less than 0.3%. Furthermore, alkali-free aluminosilicate glass fiber tape possesses characteristics such as high temperature resistance, thermal insulation, good electrical insulation, fire resistance, waterproofing, aging resistance, weather resistance, high strength, high modulus, and a smooth appearance.

[0032] Considering the weak magnetism of iron atoms, the content of Fe oxide in the glass fiber tape needs to be controlled in order to reduce the generated magnetic noise. Preferably, the iron oxide content is less than 0.1%.

[0033] Specifically, the modified resin is a modified bisphenol F type epoxy resin, the modifier is a waterborne polyurethane, and the mass ratio of bisphenol F epoxy resin to waterborne polyurethane is 9:1.

[0034] Bisphenol F epoxy resin has low viscosity, good heat resistance, water resistance and electrical properties; the elastomer properties of polyurethane materials are between those of plastics and rubber, and they are oil-resistant, wear-resistant, low-temperature resistant, aging-resistant, high in hardness and elastic; the addition of waterborne polyurethane to bisphenol F epoxy resin increases its low-temperature resistance, enabling the product to be used in ultra-low temperature operating environments.

[0035] On the other hand, this invention discloses a method for preparing a low-magnetic-noise level fiberglass Dewar liner, such as... Figure 1 , 2 As shown, it includes the following steps: Step S1: Impregnate the glass fiber tape in pure modified resin liquid and apply vacuum to fully impregnate the glass fiber tape with modified resin, remove gas inclusions, and obtain pre-impregnated glass fiber tape. Step S2: Pre-wrap polytetrafluoroethylene tape 2 around the surface of mandrel 1 and preheat mandrel 1; Step S3: Wrap the pre-impregnated glass fiber tape 3 obtained in step S1 around the outer surface of the polytetrafluoroethylene tape 2 of the preheated metal mandrel 1. Step S4: Place the spiral tube obtained in step S3 into an insulation box and cure the modified resin in the insulation box; Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after cooling, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

[0036] Specifically, in step S1 above, the glass fiber tape has a width of 20-50 mm and a thickness of 0.05-0.2 mm, wherein the mass percentage of impurities K2O+Na2O is less than 0.3% and the content of impurities iron oxide is less than 0.1%.

[0037] It should be noted that K2O and Na2O are common in glass fibers; their content directly affects the tensile strength of the glass fiber, which is a crucial factor in the practical application of Dewar liners. Therefore, the content of K2O and Na2O impurities in the glass fiber tape must be controlled, with their mass percentage being less than 0.3%. Fe oxides, due to the presence of iron atoms, still exhibit weak magnetism. Controlling the content of Fe oxides in the glass fiber tape is to reduce magnetic noise; therefore, the iron oxide content is less than 0.1%.

[0038] Specifically, the mass ratio of the glass fiber tape to the modified resin liquid in the above-mentioned pre-impregnated glass fiber tape is 5-7:3-5.

[0039] Specifically, in step 1 above, the modified resin is modified bisphenol F epoxy resin, the modifier is polyurethane, and the mass ratio of bisphenol F epoxy resin to polyurethane is 9:1.

[0040] It should be noted that the elastomer properties of polyurethane materials are between those of plastics and rubber, exhibiting oil resistance, wear resistance, low-temperature resistance, aging resistance, high hardness, and elasticity; bisphenol F type epoxy resin has low viscosity, good heat resistance, water resistance, and electrical properties; by modifying bisphenol F type epoxy resin with polyurethane, ultra-low temperature applications of Dewar materials can be achieved.

[0041] Specifically, in step S1 above, the glass fiber tape impregnation time is 2-5 hours, and the vacuum degree is 10. -2 ~10 -3 MPa.

[0042] It is important to note that the most important purpose of pre-impregnation is to remove gas from the glass fiber tape, ensuring that the gas content in the subsequently prepared FRP Dewar liner is as close to zero as possible. In existing technologies, glass fiber filaments, tapes, or cloth are typically passed continuously and rapidly through a resin solution bath. The fiber is immersed in the resin for a very short time, and there is no vacuum treatment process. This results in numerous micropores on the fiber surface, with a porosity reaching 20-40%. The presence of these pores severely affects low-temperature performance and is also the fundamental reason for the low transparency of FRP. Therefore, by using a vacuum pre-impregnation process, the modified resin fully wets the glass fiber tape, significantly reducing the porosity of the resulting FRP Dewar liner to 1-3%. This improves transparency and strength (by 15-25%), enabling thinner walls.

[0043] Specifically, in step S2 above, the mandrel is pre-wound with polytetrafluoroethylene tape in a spiral to an overlap of 30-50%, and the mandrel is preheated to 80-90°C. The overlap in this text refers to the proportion of width of the subsequent loop covering the preceding loop.

[0044] The mandrel is typically a hollow metal mandrel with polytetrafluoroethylene (PTFE) wrapped around its outer surface; PTFE tape is not required inside. Research has shown that resin-metal contact affects magnetic noise levels, a key factor in the successful fabrication of low-magnetic-noise Dewars. Avoiding direct contact between the resin and the metal mandrel helps reduce magnetic noise. This factor is often overlooked or ignored. The purpose of wrapping with PTFE tape is to prevent contact between the modified resin and the metal mandrel. The metal used in the fiberglass industry can be any type of metal mandrel. Pre-wrapping the mandrel with a PTFE film further prevents direct resin-metal contact, reducing the magnetic noise level of the inner liner.

[0045] The mandrel is preheated for 3 to 6 hours, that is, it is heated 3 to 6 hours before the pre-impregnated glass fiber tape is wound. After the heating is completed, the winding is carried out to ensure that the outer surface temperature of the mandrel reaches 80 to 90°C during the winding. The purpose of preheating is to ensure that the pre-impregnated glass fiber tape is heated evenly over the entire area while being wound, which is beneficial to the uniform curing reaction in the later stage.

[0046] Specifically, in step S3 above, the thickness of the pre-impregnated glass fiber tape is 1~6mm.

[0047] The thickness of the pre-impregnated fiberglass tape is the same as the thickness of the finished Dewar liner.

[0048] After the winding is finished, as follows Figure 2 As shown, from the innermost layer to the outermost layer are the mandrel, polytetrafluoroethylene tape, and pre-impregnated fiberglass tape.

[0049] Specifically, in step S4 above, the graded curing temperature is 80-200℃ and the curing time is 2-4 hours.

[0050] It should be noted that, for thorough and uniform curing, graded curing is preferred. Graded curing refers to curing at different temperature stages. More specifically, the modified resin is graded and cured in an insulated chamber, generally in three temperature gradients. For example, curing at 80°C for 90 minutes, at 120°C for 90 minutes, and at 160°C for 60 minutes; alternatively, curing at 80°C for 60 minutes, at 140°C for 60 minutes, and at 200°C for 60 minutes, etc.

[0051] Specifically, in step S5 above, after the modified resin has fully cured, the metal mandrel is extracted. Due to the extremely high strength of the fiberglass inner liner material and the fact that the mandrel is pre-wrapped with PTFE tape, the mandrel is easily extracted, resulting in the finished product. In practice, the mandrel can be easily removed by gently tapping the finished product once with a tool.

[0052] Specifically, the inner diameter of the inner liner obtained in step S5 is 15-250 mm, the wall thickness is 1-6 mm, and the length is 10-1100 mm.

[0053] The density of the obtained fiberglass Dewar liner was tested using a density meter (model DH-120M), and the density was found to be 1.84–1.86 g / cm³. 3 .

[0054] The obtained fiberglass Dewar liner was tested for strength and elasticity using a universal testing machine (model UTM5305). The warp tensile strength was 310–318 MPa, the weft tensile strength was 304–315 MPa, the compressive strength perpendicular to the laminations was 466–472 MPa, the shear strength parallel to the laminations was 44.5–46 MPa, the flexural strength perpendicular to the laminations was 384–387 MPa, and the flexural modulus of elasticity was 2.48–2.51 GPa.

[0055] The magnetic noise level of the obtained fiberglass Dewar liner was measured using a SQUID superconducting quantum interference device, and the magnetic noise level was 10. -14 ~10 -15 T.

[0056] This invention modifies bisphenol F epoxy resin into polyurethane by adding a modifier. The mass ratio of bisphenol F epoxy resin to polyurethane is 9:1. This modification of the resin enables the Dewar material to achieve ultra-low temperature application, i.e., at 4K temperature, without cracking or deformation, and with long-lasting stability.

[0057] This invention utilizes electronic-grade alkali-free aluminosilicate glass fiber tape. Considering that high potassium and sodium oxide content leads to low product strength and iron oxide affects magnetic noise levels, the content of potassium, sodium oxide, and iron oxide is further controlled to ensure the tensile strength of the glass fiber and achieve a low magnetic noise level.

[0058] This invention utilizes a vacuum pre-impregnation process to fully wet the glass fiber tape with modified resin, thereby reducing the porosity of the Dewar liner by 1-3%. Compared to the 20-40% porosity of non-vacuum impregnation, this invention reduces the porosity by 85%-98%, increases the strength by 15-25%, and achieves thinner walls.

[0059] This invention uses a pre-wrapped polytetrafluoroethylene (PTFE) film on the mandrel to avoid direct contact between the resin and the metal mandrel, thereby reducing the magnetic noise level of the inner liner. After cooling, the PTFE film can be removed from the inner liner to obtain the finished product.

[0060] Example 1 This embodiment provides a method for preparing a fiberglass Dewar liner with low magnetic noise level, resulting in a fiberglass Dewar liner with low magnetic noise level. Specific details are as follows: Step S1: The modified resin liquid is obtained by mixing bisphenol F epoxy resin and waterborne polyurethane in a mass ratio of 9:1; Step S2: Impregnate the glass fiber tape in the modified resin liquid obtained in step S1, with a mass ratio of glass fiber tape to modified resin of 7:3; and apply a vacuum, subjecting the glass fiber tape to a vacuum of 10... -2 Pre-impregnated for 5 hours under MPa vacuum conditions, gas inclusions are removed to obtain pre-impregnated glass fiber tape; Step S3: Pre-wrap polytetrafluoroethylene (PTFE) tape around the surface of a 100mm diameter mandrel, with an overlap of 30% between adjacent PTFE tape layers; then preheat the mandrel to 80℃. Step S4: The pre-impregnated glass fiber tape obtained in step S1 is wound onto the mandrel under a process tension of 0.5 MPa, with a winding thickness of 3 mm. Step S4: Place the spiral tube obtained in step S3 into an insulation box and perform graded curing of the modified resin in the insulation box. Curing is carried out at 80°C for 30 minutes, at 120°C for 30 minutes, and at 150°C for 60 minutes. Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after natural cooling, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

[0061] The fiberglass Dewar liner obtained in Example 1 has an inner diameter of 100mm, a wall thickness of 3mm, and a length of 1100mm.

[0062] The fiberglass Dewar liner obtained in Example 1 was tested using a density meter (model DH-120M), and the density was measured to be 1.85 g / cm³. 3 .

[0063] The fiberglass Dewar liner obtained in Example 1 was tested for strength and elasticity using a universal testing machine, model UTM5305. The warp tensile strength was 312 MPa, the weft tensile strength was 305 MPa, the vertical compressive strength was 468 MPa, the parallel shear strength was 45 MPa, the vertical bending strength was 385 MPa, and the bending modulus of elasticity was 2.50 GPa.

[0064] The fiberglass Dewar liner obtained in Example 1 had its magnetic noise level measured using a SQUID superconducting quantum interference device, and the magnetic noise level was 10. -14 T.

[0065] Example 2 This embodiment provides a method for preparing a fiberglass Dewar liner with low magnetic noise level, resulting in a fiberglass Dewar liner with low magnetic noise level. Specific details are as follows: Step S1: The modified resin liquid is obtained by mixing bisphenol F epoxy resin and waterborne polyurethane in a mass ratio of 9:1; Step S2: Impregnate the glass fiber tape in the modified resin liquid obtained in step S1, with a mass ratio of glass fiber tape to modified resin liquid of 5:5; and apply a vacuum, subjecting the glass fiber tape to 10... -3 Pre-impregnated for 4 hours under MPa vacuum conditions, gas inclusions are removed, and pre-impregnated glass fiber tape is obtained; Step S3: Pre-wrap the surface of the 150mm diameter mandrel with polytetrafluoroethylene tape, one layer is sufficient, with an overlap of 50%; then preheat the mandrel to 85℃; Step S4: The pre-impregnated glass fiber tape obtained in step S1 is wound onto the mandrel under a process tension of 0.5 MPa, with a winding thickness of 5 mm; Step S4: Place the spiral tube obtained in step S3 into an insulation box and perform graded curing of the modified resin in the insulation box. Curing is carried out at 90°C for 40 minutes, at 120°C for 60 minutes, and at 160°C for 90 minutes. Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after cooling, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

[0066] The fiberglass Dewar liner obtained in Example 2 has an inner diameter of 150 mm, a wall thickness of 5 mm, and a length of 1100 mm.

[0067] The fiberglass Dewar liner obtained in Example 2 was tested using a density meter (model DH-120M), and the density was measured to be 1.86 g / cm³. 3 .

[0068] The fiberglass Dewar liner obtained in Example 2 was tested for strength and elasticity using a universal testing machine, model UTM5305. The warp tensile strength was 318 MPa, the weft tensile strength was 315 MPa, the compressive strength perpendicular to the layer was 472 MPa, the shear strength parallel to the layer was 46 MPa, the flexural strength perpendicular to the layer was 387 MPa, and the flexural modulus of elasticity was 2.48 GPa.

[0069] The fiberglass Dewar liner obtained in Example 2 had its magnetic noise level measured using a SQUID superconducting quantum interference device, and the magnetic noise level was 10. -15 T.

[0070] Example 3 This embodiment provides a method for preparing a fiberglass Dewar liner with low magnetic noise level, resulting in a fiberglass Dewar liner with low magnetic noise level. Specific details are as follows: Step S1: The modified resin liquid is obtained by mixing bisphenol F epoxy resin and waterborne polyurethane in a mass ratio of 9:1; Step S2: Impregnate the glass fiber tape in the modified resin liquid obtained in step S1, with a mass ratio of glass fiber tape to modified resin of 3.5:6.5; and apply a vacuum, keeping the glass fiber tape at 10°C. -3 Pre-impregnate for 3.5 hours under MPa vacuum conditions to remove gas inclusions and obtain pre-impregnated glass fiber tape; Step S3: Pre-wrap PTFE tape around the surface of the 230mm diameter mandrel, with an overlap of 40% between adjacent PTFE tape layers; then preheat the mandrel to 90℃. Step S4: The pre-impregnated glass fiber tape obtained in step S1 is wound onto the mandrel under process tension, with a thickness of 6 mm. Step S4: Place the spiral tube obtained in step S3 into an insulation box and perform graded curing of the modified resin in the insulation box. Curing is carried out at 80°C for 60 minutes, at 120°C for 60 minutes, and at 160°C for 60 minutes. Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after cooling and curing, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

[0071] The fiberglass Dewar liner obtained in Example 3 has an inner diameter of 230 mm, a wall thickness of 6 mm, and a length of 1100 mm.

[0072] The fiberglass Dewar liner obtained in Example 3 was tested using a density meter (model DH-120M), and the density was measured to be 1.84 g / cm³. 3 .

[0073] The fiberglass Dewar liner obtained in Example 3 was tested for strength and elasticity using a universal testing machine, model UTM5305. The warp tensile strength was 310 MPa, the weft tensile strength was 304 MPa, the compressive strength perpendicular to the layer was 466 MPa, the shear strength parallel to the layer was 44.5 MPa, the flexural strength perpendicular to the layer was 384 MPa, and the flexural modulus of elasticity was 2.51 GPa.

[0074] The fiberglass Dewar liner obtained in Example 3 had its magnetic noise level measured using a SQUID superconducting quantum interference device, and the magnetic noise level was 10. -14 T.

[0075] It should be noted that the longitudinal tensile strength referred to in this article is the tensile strength along the circumference of the inner liner, the latitudinal tensile strength is the tensile strength along the generatrix of the inner liner, the vertical compressive strength is the compressive strength perpendicular to the inner liner wall, the parallel shear strength is the shear strength parallel to the inner liner wall, and the vertical layer bending strength is the bending strength perpendicular to the inner liner wall.

[0076] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A low-magnetic-noise level fiberglass Dewar liner, characterized in that, By weight percentage, the inner liner comprises: 50-70% fiberglass tape and 30-50% modified resin; the magnetic noise level of the fiberglass Dewar inner liner is 10. -14 ~10 - 15 T; The modified resin is a modified bisphenol F type epoxy resin, the modifier is polyurethane, and the mass ratio of bisphenol F type epoxy resin to polyurethane is 9:

1. The glass fiber tape is an alkali-free aluminosilicate glass fiber tape; the K2O+Na2O mass percentage of the glass fiber tape is less than 0.3%, and the iron oxide content is less than 0.1%; the warp tensile strength of the fiberglass Dewar liner is 310-318 MPa, and the weft tensile strength is 304-315 MPa.

2. A method for preparing a low-magnetic-noise level fiberglass Dewar liner, characterized in that, The method for preparing the low magnetic noise level fiberglass Dewar liner according to claim 1 includes the following steps: Step S1: Impregnate the glass fiber tape with a modified resin liquid and apply a vacuum to ensure the modified resin fully impregnates the glass fiber tape, remove gas inclusions, and obtain a pre-impregnated glass fiber tape; wherein the vacuum degree is 10. -2 ~10 -3 MPa; Step S2: The surface of the metal mandrel is pre-wrapped with polytetrafluoroethylene tape, and then the mandrel is preheated to 80~90℃ for 3~6 hours; Step S3: Wrap the pre-impregnated glass fiber tape obtained in step S1 around the outer surface of the polytetrafluoroethylene tape of the preheated metal mandrel; Step S4: Place the spiral tube obtained in step S3 into an insulation box and cure the modified resin in the insulation box; Step S5: After the modified resin has fully cured, the metal mandrel is pulled out; after cooling, the irregular ends are cut off with a water jet to obtain the finished fiberglass Dewar liner.

3. The preparation method according to claim 2, characterized in that, In step S1, the glass fiber tape has a width of 20-50 mm, a thickness of 0.05-0.2 mm, a K2O+Na2O mass percentage of less than 0.3%, and an iron oxide content of less than 0.1%.

4. The preparation method according to claim 2, characterized in that, In step S1, the mass ratio of the pre-impregnated glass fiber tape to the modified resin liquid is 5-7:3-5; the impregnation time of the glass fiber tape is 2-5 hours.

5. The preparation method according to claim 2, characterized in that, In step S2, the mandrel is pre-wound with polytetrafluoroethylene tape, and the overlap of the spiral winding is 30-50%.

6. The preparation method according to claim 2, characterized in that, In step S3, the pre-impregnated glass fiber tape is wound around the outer surface of the polytetrafluoroethylene tape of the preheated metal mandrel, with a process tension of 0.5 MPa. The thickness of the pre-impregnated glass fiber tape is 1~6mm.

7. The preparation method according to claim 2, characterized in that, In step S4, the curing temperature is 80-200℃ and the curing time is 2-4 hours.

8. The preparation method according to claim 2, characterized in that, The inner liner obtained in step S5 has an inner diameter of 15–250 mm, a wall thickness of 1–6 mm, a length of 10–1100 mm, and a magnetic noise level of 10. -14 ~10 -15 T.

Citation Information

Patent Citations

  • Nonmetal magnetism-free liquid nitrogen dewar

    CN102661482A

  • Aeromagnetic survey device based on low-temperature superconductive SQUID

    CN105785288A

  • Low-temperature system and superconducting quantum interference system

    CN112946761A

  • Glass fiber degassing and winding method

    CN102059807A

  • Airtight reinforcing material for extremely low temperature container

    JP2002307612A